2018
DOI: 10.5267/j.ccl.2018.8.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thiophene-pyrazole conjugates as potent antimicrobial and radical scavengers

Abstract: The current study presents the synthesis of thiophene-appended pyrazoles through 3+2 annulations of chalcones 3(a-g) with aryl hydrazine hydrochlorides 4(a-d) in acetic acid (30%) under reflux conditions produced the thiophene-pyrazole hybrids 5(a-g) in good yields. Structures of synthesized new pyrazoles were confirmed by spectral studies, and elemental analysis. Further, preliminary biological evaluation studies show that compounds 5b and 5f having chloro substitution only in the thiophene ring exhibited exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…M. G. Prabhudeva et al, in 2018 reported the synthesis of bioactive thiophene-pyrazole conjugates and screened further for their antimicrobial and anti-oxidant properties. Their biological evaluation studies showed that compounds containing chloro substitution only in the thiophene ring exhibited excellent inhibition against all the tested organisms in comparison with that of the standard drug ciproflaxin [32].…”
Section: Introductionmentioning
confidence: 99%
“…M. G. Prabhudeva et al, in 2018 reported the synthesis of bioactive thiophene-pyrazole conjugates and screened further for their antimicrobial and anti-oxidant properties. Their biological evaluation studies showed that compounds containing chloro substitution only in the thiophene ring exhibited excellent inhibition against all the tested organisms in comparison with that of the standard drug ciproflaxin [32].…”
Section: Introductionmentioning
confidence: 99%
“…Claisen-Schmidt condensation of 2-acetyl-5-chlorothiophene with substituted benzaldehydes afforded a series of chalcone analogs, which underwent cyclocondensation with two phenylhydrazines to give pyrazolines 45 (Figure 5), whose antimicrobial activity was examined. [54] Compounds…”
Section: Thiophene-substituted Azolesmentioning
confidence: 99%
“…Claisen–Schmidt condensation of 2‐acetyl‐5‐chlorothiophene with substituted benzaldehydes afforded a series of chalcone analogs, which underwent cyclocondensation with two phenylhydrazines to give pyrazolines 45 (Figure 5), whose antimicrobial activity was examined. [ 54 ] Compounds 45 (R 1 = R 2 = OCH 3 ; R = H, R 1 = R 2 = CH 3 ; R = H) had a broad spectrum activity, being at least equipotent to ciprofloxacin (MIC = 12.5–25 μg/ml) and nystatin (MIC = 25–50 μg/ml) against all the microbial strains under investigation. In addition, pyrazoline 45 (R 1 = R 2 = OCH 3 ; R = Cl) was equipotent to ciprofloxacin (12.5 μg/ml) against P. aeruginosa , while pyrazoline 45 (R 1 = N(CH 3 ) 2 ; R 2 = H; R = Cl) was equipotent to nystatin (12.5 μg/ml) against C. albicans .…”
Section: Antimicrobial Compounds Based On Thiophene‐substituted Heter...mentioning
confidence: 99%
“…Synthesis of pyrazoles substituted by thiophene moiety 29 could be carried during the reaction of chalcone-type compound 28 with phenyl hydrazine hydrochloride 4 -HCl via 3 + 2 annulations ( Scheme 13 ). The obtained thiophene-pyrazole hybrids 29 were screened as antimicrobial and antioxidant agents ( Scheme 13 ) [ 50 ].…”
Section: Synthesis Of Pyrazolesmentioning
confidence: 99%